Implementation Of FMEA On The Potential Of Medication Error In Pharmaceutical Services In Bonang II In Primary Health Care Demak Regency - Suwarni, Sri; Haryanti, Nur; Gloria, Fransisca (STIKES Telogorejo Semarang, 2023)
Pharmaceutical service is one of the high risk areas in supporting the quality of health services, not least in the pharmacy service at Puskesmas. Failure Mode and Effect Analysis (FMEA) is one method that can be used to detect the existence of medication error, so it can be designed an action to minimize the risk of medication error in the pharmaceutical service. This research is a research action researched by applying FMEA method. This research was conducted in cross sectional, with prospective data taking on recipes in Pharmacy Room of Puskesmas Bonang II of Demak Regency in December 2017 and post implementation in February 2018. FMEA method in this research is expected to minimize the possibility of medication error in pharmacy service at Puskesmas Bonang II of Demak Regency. Through the FMEA method known RPN value before implementation for failure to read dosage dosage on an incomplete prescription is 420, the RPN value for failure to read the name of the drug on an unclear prescription is 486, in the failure mode fault filed the drug RPN value before implementation is 360. Measures implemented under the FMEA are the application of Standard Operating Procedure (SOP) prescribing, agreement on the use of abbreviations in recipes and the use of medicinal information systems of Puskesmas. The result of evaluation after FMEA implementation is reduced RPN value on failure to read dosage dose to 280, RPN value for failure to read drug name after implementation to 378, and failure mode error of taking drug name RPN value to 270.